Studying the importance of communication management strategies in addressing internal communication crises among customer service officers in Malaysia: a conceptual paper - Ahmad, Nurbarirah; Sakarji, Siti Rosnita; Mohd Nor, Khalijah; Mohd Beta, Raja Mayang Delima; Abdullah Thani, Ayu Kamareenna (2023)
Employees who are satisfied are less likely to quit, neglect work, and produce defective products, and they are more likely to remain loyal to the bank. Effective communication management is essential for attaining employee satisfaction. Consequently, the primary purpose of this study is to determine the value of communication management strategies during an internal communication crisis among Malaysian customer service officers. Employing in- depth interviews and focus groups with Malaysian employees from a variety of sectors, qualitative research methods are utilized to achieve this objective. The study's findings are anticipated to serve as a paradigm for communication management practices in the financial services industry's handling of internal communication crises. By devising the Communication Management Strategies Model for internal communication crisis management, organizations can mitigate the negative effects of such crises, such as employee stress, anxiety, and low morale. This investigation is also intended to benefit the public and private sectors, as well as employees.